Board Game Putri Kembang Dadar Sebagai Media Edukatif Bagi Remaja Di Kota Palembang - Dimas Fernando; Heri Iswandi; Hestia Rachmat Nunciata (VisArt: Jurnal Seni Rupa dan Design, 2025)
Folklore constitutes an essential part of cultural heritage, encompassing educational, moral, and historical values that enrich knowledge and contribute to the character development of younger generations. These stories not only convey positive messages but also reflect the identity and local wisdom of a region. However, the rapid advancement of technology and the widespread influence of modern culture have led to a significant decline in adolescents’ interest in folklore. This condition presents a challenge in the efforts to preserve and raise awareness of local culture, particularly the folklore of Palembang. This study aims to design an engaging educational medium in the form of a board game, adapted from the folk tale Putri Kembang Dadar. The primary objective is to increase teenagers’ interest in and understanding of folklore while strengthening their appreciation of local cultural identity. The design process employs the Design Thinking approach, which involves the stages of problem identification, solution formulation, and the application of visually appealing concepts that align with contemporary youth interests. The final product is an interactive and educational board game, presented in an engaging and accessible format. The achievement of this design is expected to be able to introduce and provide education for teenagers in Palembang City regarding the cultural heritage in the form of the Putri Kembang folk tale.